The gethnic approach for explaining the search for health information on social media. (30th September 2020) - Rosenberg, D; Mano, R; Mesch, G
Abstract: Gender and ethnic inequalities in searching for health information have been studied extensively in the context of the internet as a whole, but rarely with respect to social media. Moreover, locality size has rarely been considered as a determinant in the search for health information. Furthermore, little attention has been paid to differences between searching for health information in general and for information on specific health issues. This study proposes a gethnic diversification approach to understand these phenomena. This approach maintains that the triple disadvantage of belonging simultaneously to three disadvantaged groups is translated into an advantage with respect to the probability of searching for health information online. The sample consisted of social media users in Israel (N = 803). The study's outcomes variables were general types of health information (medical vs. non-medical) and searching for specific health issues. The results of logistic regression analyses provide support for the gethnic diversification approach. These results imply that disadvantaged minorities residing in small localities (but also in large ones) use social media to search for health information to a greater extent than their counterparts from larger localities and than members of the advantaged group in order to compensate for their restricted amount of health-related social capital. This finding signals a major need for accessible and quality health services in small localities where many disadvantaged minority groups reside. Key messages: Minority women residing in small localities should be treaten as a special group by the public health officials. More resources should be invested in developing health services in localities populated by minorities.